Identity Security Threats: An Analysis Of The Speech Act In Donald Trump Military Excellence Policy - Septiyana Razak Priyatna; Maulana Rifai (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
This study examines the policy of military excellence under the administration of Donald Trump, 2.0. This study uses a descriptive qualitative method with an approach; Case studies and critical discourse analysis techniques. The study examined the narrative in the text of Trump's statement, when consolidating